The Efficacy of Exercise Therapy for Nonspecific Chronic Low Back Pain According to the FITT Principle: A Systematic Review With Meta-analyses - Laura Blanco-Heras; Manuel Rebollo-Salas; Melania Cardellat-González; Alejandro Cuevas-Moreno; José-Jesús Jiménez-Rejano; Álvaro-José Rodríguez-Domínguez (Journal of Orthopaedic & Sports Physical Therapy, 2026)
OBJECTIVE: To evaluate the efficacy of exercise therapy interventions differing in frequency, intensity, type, and time (FITT) on disability in individuals with nonspecific chronic low back pain (LBP). DESIGN: Intervention systematic review with meta-analyses. LITERATURE SEARCH: Electronic databases were searched from inception to March 2026. STUDY SELECTION CRITERIA: We included randomized controlled trials (RCTs) that enrolled adults with nonspecific chronic LBP (>3 months) and compared exercise interventions differing in at least 1 FITT component and reported disability outcomes. DATA SYNTHESIS: Random-effects meta-analyses were conducted for each FITT component. Certainty of evidence was assessed using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) framework, and prediction intervals were calculated. A complementary analysis used a 0-100 disability scale, with a 15-point improvement prespecified as the minimal clinically important difference. RESULTS: Seventy RCTs (n = 3991) were included. High-frequency programs (≥3 sessions per week) showed statistically significant improvements in long-term disability compared with low-frequency programs (standardized mean difference [SMD], 0.29; 95% confidence interval [CI]: 0.09, 0.49; moderate certainty). Sensorimotor short-term (SMD, −0.49; 95% CI: −0.78, −0.21; very low certainty) and long-term (SMD, −0.76; 95% CI: −1.48, −0.03; very low certainty), yoga short-term (SMD, −0.39; 95% CI: −0.68, −0.10; moderate certainty), and assisted long-term (mean difference, −3.96; 95% CI: −5.47, −2.45; moderate certainty) exercise programs demonstrated statistically significant reductions in disability compared with other modalities. CONCLUSION: In adults with nonspecific chronic LBP, higher-frequency exercise programs were associated with improvements in disability. Sensorimotor, yoga, and assisted exercises may offer modest additional benefits. Given the low certainty and lack of clinically meaningful effects, exercise prescriptions should prioritize patient preferences, feasibility, and long-term adherence rather than a single FITT component. J Orthop Sports Phys Ther 2026;56(9):571-584. Epub 14 July 2026. doi:10.2519/jospt.2026.14098